Misogynistic Hadith in the Reading of the Liberal Islamic Network: A New Direction of Hadith Understanding - M. Nurdin Zuhdi (Brajamusti Publication, 2024)
The Liberal Islamic Network (JIL) has a unique and interesting understanding of religious texts, including Hadith. One of the themes that will be examined in this article is about its interpretation of misogynistic hadith. The question is why does JIL have a different reading of the misogynistic hadith? The purpose of writing is to find a female-friendly understanding of the hadith.. This research is a library research; the approach used is descriptive-critical analysis with qualitative methods, the theory used is mubadalah; data collection is done by exploring library data, both published in the form of books or articles by JIL which can be accessed at www.islamlib.com. The results of the study show that in JIL view, interpreting the hadith text is not enough just by looking at the sound and quality of the text alone. However, in understanding a hadith it is very important to consider rationality and logic. According to JIL, rationality and logic will help determine the objectivity of understanding a hadith. For JIL, Maqashid Al-Shari'ah is the first source of law in Islam and then followed in tandem by the Qur'an and Al-Sunnah. For JIL, Maqashid Al-Syari'ah is the core of the totality of Islamic teachings. This research recommendation for preachers, religious figures, household leaders, that in reading and understanding hadith is not enough with just one approach, but it requires integration of knowledge, including the mubadalah approach that contains the principles of humanity. Hadith is not enough to be understood only textually and bayani oriented, it needs another approach that is more rational-contextual (burhani) and friendly-wise (irfani).